A Novel Nano-Fiber of Iranian Gum Tragacanth-Polyvinyl Alcohol/Nanoclay Composite for Wound Healing Applications. (2015) - Heydary, H. Amiri; Karamian, E.; Poorazizi, E.; Khandan, A.; Heydaripour, J.
Abstract: The fibers with smaller pores and higher surface area than regular fibers have enormous applications in tissue scaffolds, protective clothing, and wound healing. Iranian Gum Tragacanth (IGT) is the most common natural polymers which has found with lots of applications recently, and has attractive characteristic like nontoxic nature, biodegradability, higher resistance, antibacterial and good biological properties to bacterial attacks. In the current work, poly vinyl alcohol (PVA)/IGT biocomposite fiber is prepared using electrospinning (ELS) method in aqueous solutions with PVA blended system in a volume ratios of 60/40, 70/30, 80/20, and 90/10 composite with different amount of nano-clay (NC) powder (1% and 3%) to enhance the chemical and mechanical stability. The blended nanofibers are characterized by scanning electron microscopy (SEM), fourier transform infrared (FTIR) techniques. The FTIR analysis indicated that PVA and IGT may be having H + bonding interactions. The current study reveals that with a higher percentage of IGT in the blend nanofibers, superior degradation, higher chemical and mechanical stability could be obtained. Moreover, the blend nanofibers with 80/20 with 3% NC exhibit improvement in unique properties compared to pure PVA/IGT.